English Training for PKK Mothers as Strategy to Assist Children Learn English from Young Age - Rohmana, Wahyu Indah Mala; Senjana, Suci (Universitas Pendidikan Ganesha, 2022)
Currently, many children are exposed to English, especially from online media, and are starting to practice it at home. Children, especially toddlers, need assistance at home from their mothers. However, not all parents especially mothers have enough English skills to teach their own children. Therefore, the community service that is carried out for PKK women in Karangploso View is expected to improve English communication by parents at home better. The community service aims to increase the English skill of the member of PKK mothers. The method used in this activity is the Participatory Action Study (PAR). From community service, you are more confident in speaking English with your child at home, you have your own way of communicating in English according to the character of your child, and your child has an increase in his daily vocabulary in English at home. It is implicated that parents especially mothers can teach English at home by themselves and get used children to start using English from a young age.